2018
DOI: 10.4239/wjd.v9.i5.72
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to self-care practices, glycemic status and influencing factors in diabetes patients in a tertiary care hospital in Delhi

Abstract: AIMTo assess the adherence to self-care practices, glycemic status and influencing factors in diabetes patients.METHODSThis was a cross-sectional observational analysis of baseline data from a quasi-experimental study conducted among 375 diabetic patients aged between 18 to 65 years at a major public tertiary care centre in New Delhi, India during February-September’ 2016. The Summary of Diabetes Self-care activities measure was used to assess medical adherence in diabetic patients. Open ended questions were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
6
43
4
Order By: Relevance
“…Studies in low-resource settings also show a higher prevalence of suboptimal glycemic control in patients on insulin compared to those on OHA despite similar or higher levels of self-reported adherence [555657]. Such findings can arise from overreporting of insulin adherence by patients, inability of patients to procure their prescribed insulin medication (low refill adherence), or the presence of inadequate self-efficacy and minimum health literacy necessary for making correct dose adjustments.…”
Section: Improving the Assessment Of Medication Adherence: Approachesmentioning
confidence: 99%
“…Studies in low-resource settings also show a higher prevalence of suboptimal glycemic control in patients on insulin compared to those on OHA despite similar or higher levels of self-reported adherence [555657]. Such findings can arise from overreporting of insulin adherence by patients, inability of patients to procure their prescribed insulin medication (low refill adherence), or the presence of inadequate self-efficacy and minimum health literacy necessary for making correct dose adjustments.…”
Section: Improving the Assessment Of Medication Adherence: Approachesmentioning
confidence: 99%
“…Various previous studies reported poor glycemic control (HbA1c >7%) in the range of 67.5 to 78.2% of diabetic patients. 12,13 Poor glycemic control was found significantly associated with duration of diabetes, age of onset, family history, antidiabetic drugs, body mass index, hypertension, lipid and fasting plasma glucose levels. 12 Higher proportion of patients with poor glycemic control at baseline in our study could be because of inadequate antidiabetic medication use and associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Such health facility congestion can potentially compromise the quality of patient–provider communication that negatively influences patients' diabetes-related knowledge. [ 22 ] Moreover, nearly three in four patients reported missing more than one of their previous six scheduled appointments. In this regard, policy interventions for initiating long-duration dispensing of diabetes-related medications warrant consideration.…”
Section: Discussionmentioning
confidence: 99%
“…This is a cross-sectional analysis of the baseline data from a quasi-experimental trial, part of a larger study that reported on the behavioral aspects of diabetes self-care. [ 22 ]…”
Section: Methodsmentioning
confidence: 99%